The Role Of Management Ownership In Moderating The Effect Of Liquidity On Firm Value - Aprih Santoso (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2022)
This study aims to analyze the role of management ownership in moderating the effect of liquidity on firm value in Manufacturing Companies on the Indonesia Stock Exchange for the 2017 – 2021 period. Using purposive sampling, 135 companies were selected as research samples. The data was processed by multiple regression analysis using help of the IBM SPSS Statistic 26 application. The results showed that liquidity had no significant positive effect on firm value. The results of testing the moderating variable indicate that management ownership does not moderate the effect of liquidity on firm value. The managerial implication is the existence of managerial policies that can be carried out by management in an effort to increase the value of the company. The level of liquidity ratio needs to be maintained in a safe position to ensure the company's ability to meet short-term obligations, but does not cause large amounts of idle funds.